Joomla! explained live lessons (sneak peek video training) - Martin, Rod (LiveLessons., 2012)
"With this video, you'll master Joomla! one easy step at a time, through a complete hands-on case study. Martin presents crystal-clear visuals, explanations, and analogies--all extensively tested with real Joomla! beginners. Joomla! Explained requires absolutely no experience with Joomla! content management, website construction, programming, scripting, or even HTML. Rod Martin and Stephen Burge have taught thousands of beginners--and thousands more who've experimented with Joomla! but haven't mastered it yet. Nobody knows more about guiding Joomla! users up the learning curve--from confusion to results. [This video covers:] understanding what Joomla! does and how it works, installing the latest version of Joomla, navigating your site's visitor and administrator areas, mastering workflows that make site creation easy, adding text, images, links, and formatting, creating efficient, usable navigation, providing contact forms, ad banners, and link directories, using modules to enable site registration and search, adding voting and other smaller 'plug-in' features."--Resource description page.